Hubungan Antara Time Management Dengan Prokrastinasi Akademik Pada Mahasiswa Yang Mengikuti Organisasi Di Universitas Bhayangkara Jakarta Raya - Nasir, Nurwahyuni; Saktiadi, Saktiadi; Sallsabilla, Goema (Peneliti.net, 2024)
Students are not only required to have academic skills, but they are also required to have non-academic skills such as the ability to work together, lead, think critically and take responsibility. Organizations are a place for students to develop their non-academic abilities and there are also many benefits that will be obtained from participating in organizational activities. No doubt with the busy activities of lectures and organizations, many students cannot divide their time and concentration properly. Time management skills are needed for students who participate in organizations so that students are able to plan time and not waste time in order to minimize the occurrence of academic procrastination. This study aims to determine the relationship between time management and academic procrastination in students who participate in organizations at Bhayangkara University, Greater Jakarta. The sampling technique used in this study was purposive sampling with a sample of 100 respondents. Measuring instruments used academic procrastination scale and time management scale. The results of this study show that the correlation coefficient between the academic procrastination variable and time management is -0.629** with a significance level of 0.000 p≤0.01, so it can be stated that there is a negative relationship between time management and academic procrastination in students who participate in organizations at University of Bhayangkara Jakarta Raya.